The introduction of fine SiC particles into a molten Al alloy matrix - Kevorkijan, Varužan (Kovine zlitine tehnologije, 1995)
The immersion of fine SiC particulates into a Al is one of the major factors hampering the commercial development of particle reinforced composites prepared by liquid metallurgy techniques. Smaller particles are generally more difficult to wet and disperse than larger particles because of their inherently greater surface area. On the other hand, smaller particles generally give MMCs with superior mechanical properties. The challenge is to control the reaction between the matrix and reinforcement particles to achieveimproved wetting so that good distribution and interfacial bonding are obtained. This paper will review the actual technological challenge of fine particulate reinforced MMC fabrication, and will describe the most promissing new processes.
Keywords: kompozitni materiali; livarstvo; omakanje; keramični delci